Successful management of priapism secondary to leukemia - a case report - Mallik, A U; Chowdhury, G M; Shameem, I A (Bangladesh Journal of Urology, 2012)
Background: Priapism due to sickle cell disease is common but rare due to leukamia. Here in we report a case of priapism secondary to leukemia, which was managed by aspiration followed by glanulocavernous shunt. Materials and Methods: A 16-year-old male presented with prolonged involun- tary painless erection of 24 hours duration. The physical examination and Doppler USG revealed low flow priapism. Blood parameter showed increase leukocyte Count indicating leukemia. We treated the patient successfully by cavernous Lavege with adrenaline, an alpha-1 adrenergic agonist, followed by glanulocaver-nous shunt. Results: Complete detumescence was achieved after second time puncture - Lavege of the cavernous. Conclusion: We conclude that priapism due to leukemia can be best treated With adrenaline lavege until full detumescence achieved. BJU 2010; 13(2): 80-82